A Research Agenda for Microclimate Ecology in Human-Modified Tropical Forests - Jucker, Tommaso; Jackson, Tobias D.; Zellweger, Florian; Swinfield, Tom; Gregory, Nichar; Williamson, Joseph; Slade, Eleanor M.; Phillips, Josie W.; Bittencourt, Paulo R. L.; Blonder, Benjamin; Boyle, Michael J. W.; Ellwood, M. D. Farnon; et al. (Frontiers in Forests and Global Change, 2020)
Logging and habitat fragmentation impact tropical forest ecosystems in numerous ways, perhaps the most striking of which is by altering the temperature, humidity and light environment of the forest – its microclimate. Because local‐scale microclimatic conditions directly influence the physiology, demography and behavior of most species, many of the impacts of land-use intensification on the biodiversity and ecosystem functioning of tropical forests have been attributed to changes in microclimate. However, the actual pathways through which altered microclimatic conditions reshape the ecology of these human-modified ecosystems remain largely unexplored. To bridge this knowledge gap, here we outline an agenda for future microclimate research in human-modified tropical ecosystems. We focus specifically on three main themes: the role of microclimate in shaping (i) species distributions, (ii) species interactions and (iii) ecosystem functioning in tropical forests. In doing so we aim to highlight how a renewed focus on microclimate can help us not only better understand the ecology of human-modified tropical ecosystems, but also guide efforts to manage and protect them.